MEANING OF INSTRUMENTS APEIN THE LIFE OF THE KENYAH DAYAK TRIBE - Damri A Hanaou; Dewi Tika Lestari; Junita Batubara (RADJA PUBLIKA, 2025)
Sapeis a traditional musical instrument of the Dayak Kenyah people which not only functions as a means of entertainment, but also becomes an important symbol in various traditional rituals of the Dayak Kenyah people. This study aims to analyze the meaning of musicSapein the context of Dayak Kenyah cultural rituals. With a qualitative approach and ethnomusicological approach, this study combines field observations, in-depth interviews, and literature reviews. The findings show thatSapenot only accompanies traditional rituals, but also has a socio-spiritual function in strengthening community relations, cultural identity, and the continuity of tradition. Dayak Kenyah is one of the sub-tribes of the Dayak group that inhabits the interior of Kalimantan, especially in East Kalimantan and North Kalimantan, with a distribution that is also found in the border region of East Malaysia (Sarawak). In the life of the Dayak Kenyah community, musicSapehas a very special place. Not only is it a part of artistic expression,Sapealso integrated into religious rites, traditional ceremonies such as harvest festivals, welcoming guests, and various spiritual processions that are full of meaning. This musical instrument is considered a medium of spiritual communication and a means of inheriting ancestral values. Through the plucking of its notes,Sapebe an intermediary in conveying prayers, hopes and respect for the spirits of ancestors. This study specifically focuses on the Dayak Kenyah community, to highlight howSapenot only maintained as a cultural heritage, but also brought to life in the daily lives of the community as an identity that unites and strengthens solidarity amidst the increasingly rapid flow of modernization. Thus, this study emphasizes the importance of traditional music such asSape, not only as a cultural artifact but as part of cultural identity.